Battle of Ambarawa from the perspective of the universe war strategy - Syamsul Hilal; Afrizal Hendra; Tri Legionosuko (Strategi Perang Semesta, 2022)
The battle in Ambarawa was reasonably crucial in the history of the Struggle of the Indonesian nation because the battle of Ambarawa was one of a series of events to maintain independence during the revolution. How the application of the universal war strategy in the battle of Ambarawa is carried out by the warrior figures and the goals to be achieved in Palagan Ambarawa, and the impact resulting from the battle becomes the goal of this historical research in addition to making historical knowledge that may one day be lost. The method used in this study is a historical method that follows the flow from heuristic steps, source criticism, interpretation, and historiography. The Universal People's War Strategy or Incumbent System with Supit Urang tactics applied to the Battle of Ambarawa brought success and victory, apart from the factors of the superiority of infantry tactics and techniques, the superiority of the number of personnel deployed, the management of field administration operations Field logistics and better field health and the integration of operations involving all components of the nation. The victory in the battle in Ambarawa had a significant positive impact on the Struggle for the nation's daughters in cultivating a sense of trust in one's strength in continuing his Struggle, both militarily and politically.